Some aspects of the use of cloud computing in the training of physics teachers - Vladyslav Ye. Velychko; Elena G. Fedorenko; Nataliia V. Kaidan; Vadym P. Kaidan (Academy of Cognitive and Natural Sciences, 2022)
The specifics of the training of physics teachers lies in the extensive use of experimental research. E-learning, the role of which has increased due to quarantine restrictions, has the means of experimental research in its arsenal. The international educational community has developed and uses a variety of electronic educational resources, which are integrated into collections and libraries. The professional training of physics teachers is not an exception. Electronic educational resources make it possible not only to deliver educational material in a variety of ways, sometimes impossible without ICT, but also to simulate events and processes for their wider study in educational purposes. The use of cloud calculations in the form of virtual laboratory workshops is a way to solve existing problems in the training of future physics teachers. The use of cloud calculations in the educational activities of future physics teachers contributes not only to the improvement of educational material but also to the improvement of digital competence of all participants of the educational process. The research analyzed the available virtual laboratory practices, the scheme of using physics simulations was suggested, the examples of their use during physics teaching and the role of cloud calculations in the training of physics teachers were given. An analysis of the use of cloud computing and the best practices of this activity is carried out.